Penyuluhan Hukum Tentang Kekerasan Dalam Rumah Tangga (KDRT) Di Kelurahan Palabusa Kecamatan Lea-Lea Kota Baubau - Rizki Mustika Suhartono; Wa Ode Al Zarliani; Indah Kusuma Dewi; Ernawati Ernawati; Widiyanti Widiyanti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Counseling to the community aims: (1) To provide an understanding of Law Number 23 concerning Domestic Violence; (2) To provide an understanding of forms of legal protection for victims of domestic violence; (3) To provide an understanding to the public about criminal acts of domestic violence. Counseling activities in the community are motivated by phenomena that occur in the community. The problem of domestic violence itself is actually a problem that often occurs in married life, but some people do not consider what they experience as an act that is wrong in the eyes of the law. Therefore, the community needs to be given an understanding of domestic violence, so that if it occurs or experiences domestic violence, the victim can take legal steps. The method used is a participatory method which is expected to play an active role in legal counseling activities in the form of; (1) Lecture on the Socialization of Law Number 23 of 2004 concerning Domestic Violence; (2) Legal counseling regarding the material of Law Number 23 of 2004 concerning Domestic Violence; (3) Question and answer session about domestic violence through mediation.